Two forms of acetylcholine receptor gamma subunit in mouse muscle. - Mileo, A M (1995)
Nicotinic acetylcholine receptors (nAcChoRs) of skeletal muscle are heterosubunit ligand-gated channels that mediate signal transmission from motor nerves to muscle. While cloning murine nAcChoR subunits, to gain an insight into the receptor diversity across species, we detected two forms of gamma subunits in the myogenic C2C12 cell line. Both forms are functional when expressed in Xenopus oocytes. One gamma subunit [long gamma (gamma 1)] was almost identical to that previously cloned in the murine BC3H-1 tumor cell line. The second form of gamma subunit [short gamma (gamma s)] lacked 156 bp (52 amino acids) in the extracellular N terminus, adjoining the hydrophobic segment M1, which corresponds to the fifth exon of the gamma-subunit gene. The two forms of gamma subunit coexist during myogenesis in vitro and in 17-day embryonic and denervated adult muscle fibers in vivo. However, the gamma s variant was the only form of gamma subunit in newborn muscle. In dissociated muscle fibers of newborn mice, AcCho-evoked channel openings were more prolonged when compared with C2C12 myotubes or denervated adult muscle fibers. The gamma s subunit may, thus, contribute to the structural and functional diversity of nAcChoRs in muscle cells.